Combination of Pitavastatin and melatonin shows partial antineoplastic effects in a rat breast carcinoma model - Kubatka, Peter; Bojková, Bianka; Kassayová, Monika; Orendáš, Peter; Kajo, Karol; Výbohová, Desanka; Kružliak, Peter; Adamicová, Katarína; Péč, Martin; Stollárová, Nadežda; Adamkov, Marián (Acta histochemica, 2014)
Our previous results indicated significant tumor-suppressive effects of different statins in rat mammary carcinogenesis. The purpose of this experiment was to examine the chemopreventive effects of Pitavastatin alone and in combination with the pineal hormone melatonin in the model of N-methyl-N-nitrosourea-induced mammary carcinogenesis in female Sprague-Dawley rats. Pitavastatin was administered dietary (10mg/kg) and melatonin in an aqueous solution (20μg/ml). Chemoprevention began 7 days prior to carcinogen administration and subsequently continued for 15 weeks until autopsy. At autopsy, mammary tumors were removed and prepared for histopathological and immunohistochemical analysis. Compared to controls, Pitavastatin alone reduced average tumor volume by 58% and lengthened latency by 8 days; on the other hand, the drug increased tumor frequency by 23%. Combined administration of Pitavastatin with melatonin decreased tumor frequency by 23%, tumor volume by 44% and lengthened tumor latency by 5.5 days compared to control animals. The analysis of carcinoma cells showed significant increase in caspase-3 expression in both treated groups and a tendency of increased caspase-7 expression after Pitavastatin treatment alone. Significant expression decrease of Ki67 was found in carcinoma cells from both treated groups. Compared to control carcinoma cells, Pitavastatin alone increased VEGF expression by 41%, however melatonin totally reversed its undesirable effect. Pitavastatin combined with melatonin significantly increased femur compact bone thickness in animals. Pitavastatin alone decreased plasma triglycerides and total cholesterol levels, however it significantly increased levels of glucose. In summary, our results show a partial antineoplastic effect of Pitavastatin combined with melatonin in the rat mammary gland carcinoma model.
Keywords: zvířata; nádory mléčné žlázy u zvířat; melatonin; Quinolines; Animals; Breast Neoplasms; nádory prsu; ženské pohlaví; chinoliny; protokoly protinádorové kombinované chemoterapie; Rats; Antineoplastic Combined Chemotherapy Protocols; experimentální nádory mléčných žláz; Melatonin; Mammary Neoplasms, Experimental; Antineoplastic Agents; Female; Mammary Neoplasms, Animal; protinádorové látky; krysa rodu Rattus